Assessment of Thyroid Disorders in Infertile Women at a tertiary care center of Nepal - Shilpakar, Bhawani; Adhikari, Shree Prasad; Sedhain, Nesuma; Thapa, Jwala; Maskey, Suvana (Grande Medical Journal, 2025)
Background: Infertility refers to the inability to conceive after 12 months of unprotected sexual activity, is an increasing public health issue in Nepal, affecting 7.4–9.1% of reproductive-aged women. Thyroid hormones play a vital role in normal reproductive function, impacting folliculogenesis, ovulation, and implantation. Thyroid dysfunction, especially hypothyroidism, can cause irregular menstrual cycles, lack of ovulation, and difficulties in getting pregnant. This study aimed to determine the prevalence and pattern of thyroid disorders among infertile women in Nepal.Method: A hospital-based, Cross-sectional study was conducted at the Department of Infertility, Paropakar Maternity and Women’s Hospital, Kathmandu, from June 17 to September 16, 2025. A total of 109 infertile women aged 18–45 years with at least one patent fallopian tube were included using non- probability consecutive sampling method. Serum levels of TSH, FT3, and FT4 were measured using chemiluminescence immunoassay. Data were analyzed using SPSS version 27, and associations between thyroid status and clinical variables were assessed using Chi-square (χ2) test.Result: Among 109 participants, 23 (21.1%) had thyroid dysfunction. Subclinical hypothyroidism was the most common (69.6%), followed by overt hypothyroidism (26%) and subclinical hyperthyroidism (4.3%). No cases of overt hyperthyroidism were observed. A significant association was found between thyroid status and age group (p = 0.04), but not with BMI, type of infertility, ethnicity, education, occupation, or tubal status.Conclusion: Thyroid disorders were prevalent in about one-fifth of infertile women, with subclinical hypothyroidism as the predominant abnormality. As thyroid dysfunction is easily diagnosable and treatable, routine thyroid function testing should be an integral part of infertility evaluation to enhance reproductive outcomes in Nepal.